Biological heterogeneity of cancer - Fidler, Isaiah J. (Landes Bioscience, 2012)
Despite significant improvements in diagnosis, surgical techniques, and advancements in general patient care, the majority of deaths from cancer are caused by the continuous growth of metastases that are resistant to conventional therapies. In a large number of cancer patients, metastasis may well have occurred by the time of diagnosis. The metastases can be located in different distant organs and in different regions within a single organ. The major obstacle for the eradication of metastases is the biologic heterogeneity of tumor cells that constitute primary cancers and metastases. Specifically, by the time of diagnosis, malignant neoplasms contain multiple cell populations with diverse biological heterogeneity in growth rate, karyotype, cell surface receptors, antigenicity, immunogenicity, maker enzymes, gene expression, sensitivity to different cytotoxic drugs, invasion, and metastasis. This biologic heterogeneity is not restricted to primary lesions. The cellular composition of metastases in the same organ or in different organs is heterogeneous, both within a single metastasis (intralesional heterogeneity) and among different metastases (interlesional heterogeneity). This heterogeneity is due to two major processes: the selective nature of the metastatic process, and the rapid evolution and phenotypic diversification of clonal tumor cell populations during progressive tumor growth resulting from inherent genetic and epigenetic instability of many clonal populations of tumor cells.